Star forming regions linked to RCW 78 and the discovery of a new IR bubble - Cappa, Cristina Elisabet (2014)
Aims. With the aim of investigating the presence of molecular and dust clumps linked to two star forming regions identified in the expanding molecular envelope of the stellar wind bubble RCW 78, we analyzed the distribution of the molecular gas and cold dust. Methods. To accomplish this study we performed dust continuum observations at 870 μm and 13CO(2-1) line observations with the Atacama Pathfinder EXperiment (APEX) telescope, using the Large Apex BOlometer CAmera (LABOCA) and SHeFI-1 instruments, respectively, and analyzed Herschel images at 70, 160, 250, 350, and 500 μm. Results. These observations allowed us to identify cold dust clumps linked to region B (that we have named the southern clump) and region C (clumps 1 and 2), and an elongated filament. Molecular gas was clearly detected linked to the southern clump and the filament. The velocity of the molecular gas is compatible with the location of the dense gas in the expanding envelope of RCW 78. We estimate dust temperatures and total masses for the dust condensations from the emissions at different wavelengths in the far-IR and from the molecular line using local thermodynamic equilibrium and the virial theorem. Masses obtained through different methods agree within a factor of 2-6. Color-color diagrams and spectral energy distribution analysis of young stellar objects (YSOs) confirmed the presence of intermediate and low-mass YSOs in the dust regions, indicating that moderate star formation is present. In particular, a cluster of IR sources was identified inside the southern clump. The IRAC image at 8 μm revealed the existence of an infrared dust bubble of 16′′ in radius probably linked to the O-type star HD 117797 located at 4 kpc. The distribution of the near-and mid-IR emission indicate that warm dust is associated with the bubble.